(untitled) (Heritage, 2024)
The paper discusses the importance and contribution of Serbian pedagogues to the affirmation of the concept of upbringing and education based on national values. The historical aspect of school reforms, which is specific to the territory of Serbia, and important for upbringing and education in that period, is also presented. Pleiades of our prominent pedagogues conceived their own interpretations and understandings of the very concept of nation and national values. The paper presents the understanding of pedagogues in the period from 1918 to 1945, namely: Miloš Milošević, Vojislav Bakić, Ljubomir Protić, Jovan Miodragović, Vićentija Rakić and Vojislav Mladenović. The mentioned pedagogues are particularly important because in a given historical period the idea of ​​the nation is problematized in a specific historical and social context.